Kim Knott's Methodological Rapprochement: From Complete Participant to Complete Observer in Islamic Studies - Ali Imron; Mubaidi Sulaeman (UAS PRESS, 2026)
This article explores Islamic studies from the insider/outsider perspective proposed by Kim Knott. It focuses on the researcher’s identity and the theoretical framework underlying insider and outsider approaches, as well as the implications of their application in contemporary Islamic studies. This approach integrates three key elements: active participation in the studied religious community (complete participant), the role of the researcher in conducting objective observation (complete observer), and the dialogical relationship between emic and etic approaches in the analysis of religion, which Kim Knott conceptualizes as rapprochement. This implies that religious research requires a dynamic adjustment between the role of a community member and that of a neutral researcher. The article concludes that the rapprochement approach developed by Kim Knott establishes a more inclusive and dialogical framework in Islamic studies, promoting deeper understanding of Islamic religion and culture and creating space for more meaningful discussion and mutual understanding among the parties involved in religious research. Furthermore, it argues that the insider/outsider perspective offers a rich and multidimensional approach to understanding Islam. By integrating participatory perspectives, objective research, and emic–etic analysis, this approach enables researchers to develop a more comprehensive and dialogical understanding of Islam in contemporary contexts.